ETV5 Silencing Produces Mesenchymal to Epithelial Transition in INS-1 (832/13) Cell Line - Díaz-López, Yael Efrén; Cázares-Domínguez, Vicenta; Arenas-Huertero, Francisco; Gutierrez-Aguilar, Ruth (Hormone and Metabolic Research, 2024)
ETV5 has been described to be involved in the epithelial to mesenchymal transition (EMT) mainly in cancer. It is known that EMT provokes cytoskeleton remodeling, improving cellular migratory, and invasive capabilities. Moreover, overexpression of ETV5 has been correlated to cancer development and this gene has been implicated in cell proliferation. However, little is known about the downregulation of ETV5 expression in a pancreatic cell line and the inverse mesenchymal to epithelial transition (MET). Therefore, we studied the implications of ETV5 silencing over the phenotype of the insulinoma INS-1 (832/13) cell line and described the MET by partial ETV5 silencing in the INS-1 (832/13) cell line. The downregulation of ETV5 expression was obtained by using ETV5 siRNA in the insulinoma rat cell line, INS-1 (832/13). Then, ETV5 knockdown provoked a MET phenotype observed by crystal violet staining and verified by immunohistochemistry against E-cadherin. Wound healing assay showed no migration, and F-actin stain revealed rearrangement of actin microfilaments. In addition, TGFβ1 and TGFβ3 were downregulated in the absence of ETV5. ETV5 silencing induces epithelial phenotype by downregulating TGFβ1 and TGFβ3 in INS-1 (832/13) cell line.
Keywords: ETV5; mesenchymal to epithelial transition (MET); β-cell; INS-1 (832/13); TGFβ1; TGFβ3